Construction and demolition waste as a raw material for wood polymer composites – Assessment of environmental impacts. (10th July 2019) - Liikanen, Miia; Grönman, Kaisa; Deviatkin, Ivan; Havukainen, Jouni; Hyvärinen, Marko; Kärki, Timo; Varis, Juha; Soukka, Risto; Horttanainen, Mika
Abstract: The European Commission's ambitious construction and demolition waste (CDW) material recovery target has placed pressure on Finland to increase its CDW material recovery rate. It has been identified that using CDW fractions, e.g. waste wood, plastic, mineral wool and plasterboard, as raw materials for wood polymer composites (WPCs) may help in reaching the CDW material recovery target. The objectives of this study were to assess the environmental impacts of WPC production using specific CDW fractions, namely wood, plastic, plasterboard and mineral wool, as raw materials, and to compare these impacts with the baseline situation where these CDW fractions are treated with conventional waste treatment methods such as landfilling and incineration. The study focused primarily on the depletion of fossil hydrocarbons and climate change. The results indicate that, when compared to the baseline situation, the environmental impacts of CDW management can be decreased when CDW fractions are used in WPC production. By substituting WPCs for plastic or aluminium, considerable environmental benefits can be achieved in terms of the aforementioned impact categories. Due to the differences in the physical and mechanical properties of WPCs compared to plastic and aluminium, WPCs cannot necessarily substitute them in a mass-based ratio of 1:1. This was acknowledged in the study by identifying minimum substitution rates for different materials. For instance, the produced WPCs should substitute at least 6% of plastic and 8% of aluminium in order to decrease the impact on climate change compared to the advanced waste management scenario. Therefore, in applications where WPCs can be used as a substitute for these materials, WPC product design and development should be prioritised. Highlights: Environmental impacts of WPC production as a part of CDW management are assessed. WPC production decreases the environmental impacts of CDW management. Virgin material substitution has strong influence on the results. The produced WPCs should primarily substitute plastic or aluminium. Substituting wood by WPCs is not environmentally recommendable.